Indonesia's Energy Diplomacy to Promote Nuclear Energy as an Alternative to Energy Security - Aprianto, Dimas; Laksmono, Rudy; Murtiana, Sri (The Republic of Indonesia Defense University, 2024)
Indonesia faces significant challenges in meeting its growing energy demand while seeking clean, sustainable, and safe energy sources. Nuclear energy is emerging as a potential alternative, supported by the country's substantial uranium reserves. However, nuclear energy development in Indonesia faces various obstacles, including public concerns regarding safety, nuclear non-proliferation issues, and high construction costs. This research aims to analyze the role of Indonesia's energy diplomacy in promoting nuclear energy to the public and internal stakeholders as a solution to improve national energy security. Qualitative research methods were used to evaluate Indonesia's internal diplomatic and promotional efforts, including document analysis and content analysis. The study examined Indonesia's bilateral and multilateral cooperation strategies, as well as its participation in international forums such as the International Atomic Energy Agency (IAEA), while focusing on domestic education and socialization efforts. A key focus was identifying challenges, opportunities, and best practices in nuclear energy diplomacy and internal promotional campaigns. The research findings highlighted the importance of comprehensive public education, strengthening international cooperation, and implementing strict safety standards in nuclear energy development. Strategic measures identified include strengthening diplomatic capacity, improving transparency and communication with domestic stakeholders, and developing national nuclear technology and regulation capacity. The research concludes that by addressing these challenges through effective energy diplomacy and structured internal promotion, Indonesia can improve its public acceptance and nuclear energy development prospects. This has the potential to ensure the safe, responsible, and sustainable utilization of nuclear energy to meet the country's long-term energy needs and contribute to global efforts in climate change mitigation